Comparison of Ultrasound and Electrical Stimulation Guidance for Onabotulinum Toxin‐A Injections: A Randomized Crossover Study. Issue 8 (7th September 2022) - Lungu, Codrin; Nmashie, Alexandra; George, Mary Catherine; Karp, Barbara I.; Alter, Katharine; Shin, Susan; Tse, Winona; Frucht, Steven J.; Wu, Tianxia; Koo, Vivian; Considine, Elaine; Norato, Gina; et al.
ABSTRACT: Background: Botulinum neurotoxin (BoNT) injection is an established therapy for limb spasticity and focal limb dystonia. Comparative benefits of injection guidance procedures have not been rigorously studied. Objectives: We compared 2 targeting techniques for onabotulinumtoxin‐A (onabotA) injection for the treatment of focal hand dystonia and upper limb spasticity: electrophysiologic guidance using electrical stimulation (E‐stim) and ultrasound (US). Methods: This was a 2‐center, randomized, crossover, assessor‐blinded trial. Participants with focal hand dystonia or upper limb spasticity, on stable onabotA therapy for at least 2 previous injection cycles, were randomly assigned to either E‐stim or US with crossover at 3 months. The primary outcome was improvement in dystonia or spasticity severity on a visual analog scale (VAS; 0–100) measured 1 month after each injection. The secondary outcome was participant discomfort assessed on a VAS. Repeated‐measures analysis of covariance was used with linear mixed‐model covariate selection. Results: A total of 19 participants (13 men) completed the study, 10 with upper limb spasticity and 9 with dystonia. Benefit was equivalent between the 2 techniques (VAS least‐square mean [LSmean] 51.5 mm with US and 53.1 with E‐stim). E‐stim was perceived as more uncomfortable by participants (VAS LSmean 34.5 vs. 19.9 for E‐stim and US, respectively). Procedure duration was similar with the 2 procedures. There were no serious adverse events related to either approach. Conclusions: US and E‐Stim localization guidance techniques provide equivalent efficacy in onabotA injections for spasticity and dystonia. US guidance injections are more comfortable for participants. Both techniques are effective guidance methods, with US potentially preferable based on participant comfort.